2006
DOI: 10.1128/mcb.26.8.3098-3105.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of a Donor Enhances Its Use during Double-Strand Break-Induced Gene Conversion in Human Cells

Abstract: Homologous recombination (HR) mediates accurate repair of double-strand breaks (DSBs) but carries the risk of large-scale genetic change, including loss of heterozygosity, deletions, inversions, and translocations. Nearly one-third of the human genome consists of repetitive sequences, and DSB repair by HR often requires choices among several homologous repair templates, including homologous chromosomes, sister chromatids, and linked or unlinked repeats. Donor preference during DSB-induced gene conversion was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 89 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…Namely, LOH-positive genes have above-average expression levels, which is consistent with the hypothesis that DNA of transcriptionally active loci is more relaxed and, hence, prone to double strand breaks (DSB), followed by repair cascade, including the recombination machinery (GonzĂĄlez-Barrera et al 2002;Cummings et al 2007). Cobitis hybrids also tend to replace the less expressed parental allele by the more expressed allele, which is in-line with growing evidence that more transcribed homoeologs are preferably utilized as templates during DSB-induced gene conversion (Schildkraut et al 2006). Finally, the prevalence of AT → GC substitutions on some LOH sites conforms to the expected GC bias in template preference (Duret and Galtier 2009;Williams et al 2015).…”
Section: Large-scale Stasis Vs Small-scale Dynamics Of Asexual Genomessupporting
confidence: 87%
See 1 more Smart Citation
“…Namely, LOH-positive genes have above-average expression levels, which is consistent with the hypothesis that DNA of transcriptionally active loci is more relaxed and, hence, prone to double strand breaks (DSB), followed by repair cascade, including the recombination machinery (GonzĂĄlez-Barrera et al 2002;Cummings et al 2007). Cobitis hybrids also tend to replace the less expressed parental allele by the more expressed allele, which is in-line with growing evidence that more transcribed homoeologs are preferably utilized as templates during DSB-induced gene conversion (Schildkraut et al 2006). Finally, the prevalence of AT → GC substitutions on some LOH sites conforms to the expected GC bias in template preference (Duret and Galtier 2009;Williams et al 2015).…”
Section: Large-scale Stasis Vs Small-scale Dynamics Of Asexual Genomessupporting
confidence: 87%
“…We may also speculate that biased retention of the C. elongatoides subgenome may reflect its special "mechanistic" properties. Several reasons for biased template preference have already been proposed, including different expression levels of orthologous alleles (Schildkraut et al 2006), different GC contents (Duret and Galtier 2009;Williams et al 2015), or the effect of maternal ancestry when maternal endonuclease systems may preferentially induce DSB on paternal chromosomes, thereby causing biased DSB repair and unequal gene conversion (Wang et al 2010). However, none of these hypotheses may sufficiently explain the prevalence of E-like LOH as the C. elongatoides subgenome possesses neither higher expression levels nor different GC content and the maternal ancestor of all studied elongatoides-taenia hybrids was C. taenia.…”
Section: Biased Genome Fractionation and Template-preferencementioning
confidence: 99%
“…Although most of the stimulatory effects of transcription on homologous recombination likely come through the generation of recombination-initiating lesions 116 , this is not the entire story. Transcription additionally seems to enhance access to the repair template in both budding yeast and human cells 117,118 . In addition to the process of transcription, the primary transcript itself may be relevant to recombination processes.…”
Section: Discussionmentioning
confidence: 99%
“…Through gene conversion, the sequences of paralogous genes are homogenized, easing the new mutations accumulated in one of the paralogous genes. It has been shown that highly-expressed genes are more likely to experience mRNA-mediated gene conversion (Weng, et al 2000; Schildkraut, et al 2006). Thus, as a group of most actively transcribed genes (Warner 1999), the repeated occurrence of gene conversion on RP genes might be due to the highly expressed nature of RP genes.…”
Section: Discussionmentioning
confidence: 99%